Antioxidant effect and inhibitory effect on nitric oxide production of sea mustard fractions from Busan, Korea - Shin, YD; Lee, JW; Lim, SY (Edelweiss Applied Science and Technology, 2024)
We investigated the chemical characteristics and nitric oxide (NO) production and antioxidant effects of sea mustard (Undaria pinnatifida) fractions obtained from Taejongdae in Busan, Korea. Dried sea mustard was extracted using different solvents, and antioxidant effects was evaluated based on the radical scavenging and DNA oxidation assays and the effect on reactive oxygen species (ROS) production. Total phenolic content was significantly higher in the 85% aq. MeOH fraction than that in the other factions. The 85% aq. MeOH fraction was more effective in scavenging free radicals than other fractions, as assessed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2.2’-azino-bis (3-ethylbenothiazoline-6-sulfonic acid) diammonium salt radical cation (ABTS) assays (P<0.05). All sea mustard fractions decreased H2O2-induced cellular ROS production compared to the control (P<0.05), however, the 85% aq. MeOH fraction exhibited the greatest inhibitory effect on ROS production among all fractions. Moreover, the 85% aq. MeOH fraction significantly inhibited genomic DNA oxidation. In addition, we measured NO levels to determine the potential anti-inflammatory effects of fractions from sea mustard and observed the highest level of activity in case of the 85% aq. MeOH fraction. These results indicated that the antioxidant effects of sea mustard are associated with its higher phenol content. This study proposes that processed food products supplemented with sea mustard can be developed into functional foods to promote the health of the local populations.